2022
DOI: 10.1161/jaha.121.022853
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Iron Deficiency and Mitochondrial Dysfunction in Advanced Heart Failure in Humans

Abstract: Background Myocardial iron deficiency (MID) in heart failure (HF) remains largely unexplored. We aim to establish defining criterion for MID, evaluate its pathophysiological role, and evaluate the applicability of monitoring it non‐invasively in human explanted hearts. Methods and Results Biventricular tissue iron levels were measured in both failing (n=138) and non‐failing control (NFC, n=46) explanted human hearts. Clinical phenotyping was complemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 63 publications
(108 reference statements)
2
27
0
Order By: Relevance
“…These suggest that iron deficiency in the heart is additionally related to a higher export and/or a lower import of iron in the cells. These assumptions about reduced DMT-1 and TfR-1 with no changes in FPN concentration were also confirmed by Zhang et al in the failing human heart [ 104 ]. Changes in the expression of iron-metabolism proteins in HF are associated with the modification of iron-regulatory factors.…”
Section: Iron Metabolism In the Failing Human Heartsupporting
confidence: 70%
“…These suggest that iron deficiency in the heart is additionally related to a higher export and/or a lower import of iron in the cells. These assumptions about reduced DMT-1 and TfR-1 with no changes in FPN concentration were also confirmed by Zhang et al in the failing human heart [ 104 ]. Changes in the expression of iron-metabolism proteins in HF are associated with the modification of iron-regulatory factors.…”
Section: Iron Metabolism In the Failing Human Heartsupporting
confidence: 70%
“…Contrarily, functional ID denotes a mismatch between tissue supply and demand for iron, mainly as a result of iron maldistribution and iron use [6]. ID causes mitochondrial dysfunction and increases the oxidative load in the myocardial cells [8], leading to impairment of the The figure is created by the author Julius Lenaerts. Adapted from Loncar et al [10].…”
Section: Figure 1: Iron Metabolism At the Cellular Levelmentioning
confidence: 99%
“…Contrarily, functional ID denotes a mismatch between tissue supply and demand for iron, mainly as a result of iron maldistribution and iron use [ 6 ]. ID causes mitochondrial dysfunction and increases the oxidative load in the myocardial cells [ 8 ], leading to impairment of the myocardial energetics and function [ 9 ] (Figure 2 ). In this article, the authors demonstrate the latest available literature on ID in heart failure (HF) patients to improve the management of this vulnerable group.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, it has been demonstrated that intravenous iron therapy with ferric carboxymaltose (FCM) administered after an episode of acute HF in patients with systemic ID (evaluated based on circulating iron parameters) can prevent recurrent HF hospitalizations [ 14 ]. The intriguing, hypothetical concept of affecting/improving myocardial energy metabolism using particular substances given orally or intravenously (such as iron formulations) requires further translational research, in particular because myocardial iron status (strictly in the heart) is not comprehensively studied [ 15 ]. It is worth mentioning that we have limited data suggesting possible improvement of skeletal muscle energetics due to iron therapy in HF patients with ID [ 16 ].…”
Section: Introductionmentioning
confidence: 99%